The Effect of Time Budget Pressure and Auditor’s Competency on Audit Quality - Yuda Muhamad Rizkia Rosadi; Irene Sukma Lestari Barus (Goodwood Publishing, 2022)
Purpose: This study aims to determine the effect of time budget pressure and auditor’s competency on audit quality. Research Methodology: The sample used in this study were auditors who work at the Public Accounting Firm in Bandung, Indonesia, and 48 auditors were asked to be respondents. The primary data was obtained by distributing questionnaires. This study uses a non-probability sampling method with a purposive sampling technique and multiple linear regression analysis methods using the Statistical Program for Society Science (SPSS) software. Results: Based on the research results, it can be concluded that the variable time budget pressure and auditor’s competence partially have a positive and significant effect on audit quality. Limitations: The limitation of this study is the variables studied consisted of only 2 (two) variables, namely time budget pressure and auditor competence. The questionnaire is distributed only to auditors who work at the Public Accounting Firm in Bandung, Indonesia. Contribution: Author, Auditor, Public Accounting Firm in Bandung City